A rare case of POEMS syndrome presenting as essential thrombocythemia. Issue 12 (16th December 2022) - Angeloudi, Elena; Pappi, Eleni; Liakos, Aris; Mainou, Maria; Vlachaki, Efthymia; Bekiari, Eleni
ABSTRACT: Polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, skin changes (POEMS) is a rare paraneoplastic syndrome, and its diagnosis is based on a series of clinical and laboratory findings. We present the case of a 46-year-old woman who was previously diagnosed with essential thrombocythemia. The patient complained about dyspnea on exertion, nausea, burning of the lower limbs, weight loss, recurrent episodes of lower back pain and polymenorrhea. Physical examination revealed hyperpigmentation, livedo reticularis of the lower limbs, sclerodermoid changes and plectrodactyly. A computed tomography-guided bone biopsy revealed the presence of plasmacytoma, and based on a combination of clinical features such as polyneuropathy, a diagnosis of POEMS syndrome has been established. The diagnosis of POEMS syndrome demands a high index of suspicion, especially in cases of peripheral neuropathy, peripheral edema or organomegaly of unknown origin. Since the syndrome can be fatal, early diagnosis is pivotal for patients' survival and quality of life.